P2P Communication among Computers and Smartphones Based on Bluetooth and Wi-Fi Direct Technologies - Venant Uzayisenga; Tri Kuntoro Priyambodo (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2020)
As result of the development of technology, most of modern computer and smartphones are Bluetooth and Wi-Fi direct wireless technologies enabled. While those wireless technologies come with the benefits of interconnecting devices without the need access point or central base station. However, computer and smartphones connected via Bluetooth based or via Wi-Fi Direct connection does not guarantee intercommunication or data transmission in meaningful way. Therefore, third party software is always needed to help for achieving data transmission. In this research an effort is done to design and develop P2P software applications and web based application by using C# and ASP.net MVC programming languages as features of Visual Studio 2017. Application would facilitate P2P communication of interconnected devices via the same channel. Built software system has been tested based on functional testing method, and usability testing. The result from functional testing shows that P2P communication meets functional requirements while usability testing has an average score of 72.2% from System Usability Scale method. The results from SUS scores brands our proposed P2P communication system to be good and highly accepted.